1. The problem statement, all variables and given/known data Given z= square root of xy, x = 2t - 1, y = 3t +4, use the chain rule to find dz/dt as a function of t. 2. Relevant equations 3. The attempt at a solution dz/dt = partial derivative of z with respect to x multiplied by dx/dt + (partial derivative of z with respect to y multiplied by dy/dt) I got that part right but how do you differentiate square root of xy as a partial derivative of z with respect to x?? Can you show me the final answer of that? Thanks!